The ’Missing Conflict’ of the Sabarmati Riverfront. Authoritarian Governance, Neoliberalism and Water in Ahmedabad, India - Pessina, Gloria (PARTECIPAZIONE E CONFLITTO, 2019)
Though the liberalization of the economy in 1991 affected India as a whole, the state of Gujarat and the city of Ahmedabad have undergone the most dramatic changes in the country. The Sabarmati Riverfront Development Project in Ahmedabad, one of the largest urban regeneration projects in India, was finalized in this context, and soon became the flagship project of the new ruling party. The article engages with the evolution of the project, reflecting on the apparent absence of a conflict that many observers would have expected to occur given the scale of the intervention, as well as its social and environmental consequences. Though some episodes of contention, related to a few controversial issues, are identified in the article, it highlights the presence of a consolidated system of power and dissent management on multiple scales. A strong ideological system combining different narratives (development, global competition, fear and security, purity and cleanliness) underpins the Sabarmati riverfront development in Ahmedabad. These narratives proved to be appealing to the local middle-class, which identifies with the message of the far-right Hindu government: respect for religious traditions, alongside an effort to conform to international development standards.